2015
DOI: 10.1007/s10903-015-0278-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Obesity and Related Diseases in African Refugees After Resettlement to United States

Abstract: Despite increases in obesity and related diseases in developing nations, initial refugee clinical visits do not address these issues. We explored the development of obesity and related diseases in a longitudinal prospective cohort of African refugees resettling in northeastern US. Using state Department of Health data, refugees were linked to a health system. Body mass index, diabetes, hypertension, and hyperlipidemia status were extracted from charts. US regional controls from NAMCS/NHAMCS data were matched b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…As a way of comparison, the prevalence among the general population globally is 3.3%, 6 4.4% and 3.6%, 7 respectively. Additionally, previous studies have indicated that refugees have higher risks of physical health issues, such as cardiovascular mortality, 8 diabetes, hypertension and hyperlipidemia 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a way of comparison, the prevalence among the general population globally is 3.3%, 6 4.4% and 3.6%, 7 respectively. Additionally, previous studies have indicated that refugees have higher risks of physical health issues, such as cardiovascular mortality, 8 diabetes, hypertension and hyperlipidemia 9 …”
mentioning
confidence: 99%
“…Additionally, previous studies have indicated that refugees have higher risks of physical health issues, such as cardiovascular mortality, 8 diabetes, hypertension and hyperlipidemia. 9 Existing evidence suggests that refugees experience a number of migration-related stressors along the migration continuum: pre-migration, in transit and post-migration stressors. 10,11 The pre-migration phase is concerned with individuals or families experiencing persecution or human rights abuses in their home countries, and who are trying to escape and find protection in a safer environment in another country.…”
mentioning
confidence: 99%
“…9,12,17,18 Although several studies have reported an increase in the prevalence of obesity and obesity-related diseases among adult refugees and an increase in their BMI trajectories after US resettlement, the data among child refugees is limited. 19,20 Two small studies demonstrated a trend toward increasing obesity prevalence among refugee children. 21,22 However, obesity risk has not been examined in a large sample of refugee children.…”
Section: What This Study Addsmentioning
confidence: 99%
“…While immigrants in Western countries have a lower BMI on arrival than native-born people, their risk to be overweight or obese slowly increases with their duration of stay, to match that of native people [9][10][11][12]. A young age at arrival seems to increase the risk of obesity [13], risk that also depends on the country of origin [11,14].…”
Section: Introductionmentioning
confidence: 99%